2015
DOI: 10.1111/cp.12040
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural group therapy for emetophobia: An open study in a psychiatric setting

Abstract: Background: Emetophobia is a neglected area within clinical research. Only

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…There were n=20 single case intervention studies that were excluded from the review as quality could not be rated based on the criteria used. Only two of the included treatment studies scored in the moderate range (Ahlen, Edberg, Di Schiena, & Bergström, 2015;Riddle-Walker et al, 2016) and the other two scored in the weak range (Klonoff, Knell, & Janata, 1984;Philips, 1985), demonstrating the lack of high quality research exploring effective interventions for SPOV.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…There were n=20 single case intervention studies that were excluded from the review as quality could not be rated based on the criteria used. Only two of the included treatment studies scored in the moderate range (Ahlen, Edberg, Di Schiena, & Bergström, 2015;Riddle-Walker et al, 2016) and the other two scored in the weak range (Klonoff, Knell, & Janata, 1984;Philips, 1985), demonstrating the lack of high quality research exploring effective interventions for SPOV.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Only four treatment studies were included in the review (Ahlen et al, 2015;Klonoff et al, 1984;Philips, 1985;Riddle-Walker et al, 2016) (Table 6). Twenty published single case studies were identified in the search and excluded.…”
Section: Treatment Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…In this journal, there are many examples of applied research studies conducted in clinical settings with representative treatment‐seeking clinical samples. For example, Ahlen, Edberg, Di Schiena, and Bergstrom () recently conducted an open trial of cognitive behavioural group therapy that was conducted in an outpatient psychiatric clinic in Stockholm, Sweden. It seems that the days of over‐controlled trials with “pure” diagnostic categories and zero client comorbidity are long gone.…”
mentioning
confidence: 99%